Laboratory 3.0: Manufacturing technologies laboratory virtualization with a student-centred methodology - Albert Fabregat-Sanjuan; Rosa Pàmies-Vilà; Francesc Ferrando Piera; Silvia De la Flor López (OmniaScience, 2017)
This paper presents a blended-learning strategy for improving the teaching method applied in the laboratory subject Manufacturing Technologies. The teaching method has been changed from a predominantly teacher-centred to an active learning system with a student-centred focus and e-learning activities. In face-to-face classes, a game-based learning platform has been used. This methodology ensured engaging classes at the same time that provided a useful live feedback for students and teachers. The virtualization of the laboratory was achieved by two different e-learning activities, self-assessment tasks and video clips. These e-learning tools have been used not only to improve the students' learning but also to enhance their motivation. The results from academic outputs show a significant improvement after the new blended learning method is applied. Moreover, a student satisfaction survey shows the positive impact of the methodology on the students' engagement and motivation.